Cortical hypertrophy with a short, curved uncemented hip stem does not have any clinical impact during early follow-up. Issue 1 (December 2015) - Maier, Michael; Streit, Marcus; Innmann, Moritz; Krüger, Marlis; Nadorf, Jan; Kretzer, J.; Ewerbeck, Volker; Gotterbarm, Tobias
Abstract Background Short stems have become more and more popular for cementless total hip arthroplasty in the past few years. While conventional, uncemented straight stems for primary total hip arthroplasty (THA) have shown high survival rates in the long term, it is not known whether uncemented short stems represent a reasonable alternative. As cortical hypertrophy has been reported for short stems, the aim of this study was to determine the radiographic prevalence of cortical hypertrophy and to assess the clinical outcome of a frequently used short, curved hip stem. Methods We retrospectively studied the clinical and radiographic results of our first 100 consecutive THAs (97 patients) using the Fitmore® hip stem. Mean age at the time of index arthroplasty was 59 years (range, 19 – 79 years). Clinical outcome and radiographic results were assessed with a minimum follow-up of 2 years, and Kaplan-Meier survivorship analysis was used to estimate survival for different endpoints. Results After a mean follow-up of 3.3 years (range, 2.0 – 4.4 years), two patients (two hips) had died, and three patients (four hips) were lost to follow-up. Kaplan-Meier analysis estimated a survival rate of 100 % at 3.8 years, with revision for any reason as the endpoint. No femoral component showed radiographic signs of loosening. No osteolysis was detected. Cortical hypertrophy was found in 50 hips (63 %), predominantly in Gruen zone 3 and 5. In the cortical hypertrophy group, two patients (two hips; 4 %) reported some thigh pain in combination with pain over the greater trochanter region during physical exercise (UCLA Score 6 and 7). There was no significant difference concerning the clinical outcome between the cortical hypertrophy and no cortical hypertrophy group. Conclusions The survival rate and both clinical and the radiographic outcome confirm the encouraging results for short, curved uncemented stems. Postoperative radiographs frequently displayed cortical hypertrophy but it had no significant effect on the clinical outcome in the early follow-up. Further clinical and radiographic follow-up is necessary to detect possible adverse, long-term, clinical effects of cortical hypertrophy.